2018
DOI: 10.1111/jeb.13262
|View full text |Cite
|
Sign up to set email alerts
|

Trait differentiation and adaptation of plants along elevation gradients

Abstract: Studies of genetic adaptation in plant populations along elevation gradients in mountains have a long history, but there has until now been neither a synthesis of how frequently plant populations exhibit adaptation to elevation nor an evaluation of how consistent underlying trait differences across species are. We reviewed studies of adaptation along elevation gradients (i) from a meta-analysis of phenotypic differentiation of three traits (height, biomass and phenology) from plants growing in 70 common garden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
163
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(180 citation statements)
references
References 101 publications
10
163
6
1
Order By: Relevance
“…We acknowledge that these metrics vary largely depending on the individuals, species and study under consideration; however, these metrics were all measured as indicators of plant reproductive output along elevations (see e.g. Halbritter et al, 2018). We only included leaf size values when it was reported as the area of the leaf (m 2 ), excluding leaf diameter, length or width.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We acknowledge that these metrics vary largely depending on the individuals, species and study under consideration; however, these metrics were all measured as indicators of plant reproductive output along elevations (see e.g. Halbritter et al, 2018). We only included leaf size values when it was reported as the area of the leaf (m 2 ), excluding leaf diameter, length or width.…”
Section: Methodsmentioning
confidence: 99%
“…Despite recent syntheses involving transplant and common‐garden experiments to elucidate patterns of plant performance and adaptation change along environmental gradients (Halbritter et al, 2018; Leimu & Fischer, 2008; Pulido et al, 2019), little efforts have been payed to summarize recent literature on the intraspecific responses along elevation across multiple reciprocal transplant experiments. Only Halbritter et al (2018) to our knowledge, reported a systematic review including transplant experiments across elevations showing significant evidence of higher biomass and survival in local individuals compared with foreign ones. However, their analysis on reciprocal transplants did not disentangle climatic variation (in temperature and precipitation) along elevation across transplant sites and focused on 22 species and 14 reciprocal transplant experiment studies available up to 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, drift, divergent selection to locally-specific conditions and/or limited variation in the source populations would lead to regionally specific patterns of foothill-alpine differentiation (3). Independently of the region of origin, alpine A. arenosa populations exhibited consistently shorter stems and larger flowers demonstrating parallelism in typical traits associated with 'alpine syndrome' that are considered adaptive in alpine environments (25,50). Elevation gradients belong to the most frequently studied environmental gradients in plant evolutionary ecology since the rise of this field (51,52), however, cases of phenotypic parallelism demonstrated by a combination of genetic and experimental data are still very rare in plant literature (53).…”
Section: Parallel Ecotypic Differentiationmentioning
confidence: 99%
“…Fine-scale environmental variation has frequently been associated with high levels of adaptive phenotypic variation. In particular, the highly heterogeneous landscapes from mountain ranges provide ample opportunity for adaptive radiation at fine spatial scales (Halbritter et al 2018; Waterhouse et al 2018). Moreover, high-altitudinal secondary valleys and cold air sinks typical of topographically complex landscapes designate topographical factors other than altitude as contributing determinants of temperature and soil moisture levels (Körner 2007; GĂŒnther et al 2016; O’Brien et al 2017; Pfennigwerth et al 2017).…”
Section: Introductionmentioning
confidence: 99%